Influence of Ethnopedagogical Materials and Problem Based Learning on Students Learning Interest and Critical Thinking - Ramlan Silaban; Grace Octavia Hutasoit; Ida Duma Riris; Marham Sitorus; Rabiah Afifah Daulay; Rafida Almira Samosir; Timotius Agung Soripada (Universitas Negeri Medan, 2025)
The cultural wealth of Indonesia has great potential in chemistry education, but it has not been optimally utilized. Materials such as reaction rates can be contextualized through traditional processes, such as the fermentation of tuak. The lack of relevant teaching materials impacts students' low interest and critical thinking skills. Therefore, an innovation in the form of ethnopedagogy-based Student Worksheets with a Problem Based Learning model is needed to create meaningful learning. This study uses a quantitative approach with a quasi-experimental method. The instruments used consist of 5 essay questions to measure critical thinking skills and a questionnaire containing 20 statements to measure learning interest. A hypothesis test was conducted using a one-tailed Independent Sample T-Test. The results show that the average learning interest of students in the experiment class is higher compared to the control class, namely 90.25 and 85.625, respectively. Meanwhile, the average posttest score for students' critical thinking ability in the experimental class reached 92.25 higher than the control class, which scored 83.5. This shows that the use of Student Worksheet based on ethnopedagogy and Problem Based Learning has an influence on students' learning interest and critical thinking.